EVALUATION OF IN-VITRO ANTIOXIDANT AND FIBRINOLYTIC ACTIVITY OF FLAVONOID-RICH FRACTION FROM THE WHOLE PLANT OF WEDELIA CHINENSIS - S, Pavithra; J, Manibala; J, Ramachandran (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The fundamental objective of this research is to evaluate the antioxidant and fibrinolytic properties of whole plant extracts of Wedelia chinensis. Methods: The extract was subjected to maceration process in an incubator for 4 hrs at 150 rotations/minute (rpm), 50°C. The plant material was left to macerate for 20 hrs. The in-vitro antioxidant property of the methanolic extract was determined using thin-layer chromatography (TLC) autobiography, 2, 2`- Azino-bis-3 ethyl benzthiazoline-6 sulfonic acid (ABTS), radical scavenging assay, metal chelating, nitric oxide, and superoxide. In-vitro thrombolytic model was performed on flavonoid fraction of W. chinensis. Results: Maximum inhibition was observed in the flavonoid fraction concentration of 20 μg/mL W. chinensis as 75.64% in ABTS radical scavenging activity, 78.0% in metal chelation, 84.34% innitric oxide radical scavenging activity, and 81.8% in super oxide radical scavenging assay. Clot lysis activity of W. chinensis was 20.43±0.34, 35.3±1.10, 43.76±0.67, and 63.42±1.65 respectively. Hemolysis rates were <5%. Conclusion: On exhaustive survey on W. chinensis, it was found that this herb has been used for various activities that potentiated the folklore use for treating mankind. Medicines derived from plant origin will have a long history of use for the prevention and treatment of various diseases. In our study, it was found that the flavonoid fraction of W. chinensis possess antioxidant and thrombolytic properties. However, in vivo clot dissolving properties and active component(s) responsible for W. chinensis are yet to be discovered which can be used to treat cardiovascular diseases. Keywords: Antioxidant, Cardiovascular diseases, Fibrinolysis, Hemolytic, Radical scavenging assay, Wedelia chinensis.